Evaluating interactive systems from an emotional perspective (2014)
In this paper, we introduce a model that aims to provide guidelines that will strengthen the evaluation of interactive systems by assisting in the identification and analysis of emotions evoked by users during system usage. We briefly discuss related projects that have included emotions in the evaluation of interactive systems. The research presented here is a preliminary work towards the inclusion of emotions during the evaluation of interactive systems. Our model is presented including details of each of its phases. We discussed preliminary results of the application of the model to evaluating a Virtual Learning Environment. Our approach comprises four major phases: Selection of relevant emotions; analysis of relationships between emotions and interactive systems; selection of detection mechanisms; and application of evaluation methods.